2014
DOI: 10.5507/bp.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a low-glycemic index vs standard diabetic diet

Abstract: Aim. There is insufficient evidence for the efficacy of a low-glycemic index (GI) diet in the management of diabetes. The goal of this study was to measure the effect of a low GI versus a standard diabetic diet in adults with diabetes type 2. Methods. This was an open label, randomized, crossover study. Twenty persons with type 2 diabetes were randomized to two groups. Each group followed a standard diabetic diet or a low glycemic index diet for 3 months. The effectiveness of the two diets was evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
(10 reference statements)
0
16
0
8
Order By: Relevance
“…Our study showed a significant reduction in HbA1c values by 0.8% with low GI preparations compared to their regular diet. However, in another study that compared the low glycemic index diet and standard diabetic diet, there was no statistically significant difference between the low GI and higher GI diets in relation to HbA1c and fasting blood glucose [29]. A study done by Yusof et al [30] showed that although the effect on HbA1c was not significantly different between the low-GI diet and the higher-GI diet or control, the improvement within the low-GI group was more pronounced and of clinical benefit.…”
Section: Discussionmentioning
confidence: 91%
“…Our study showed a significant reduction in HbA1c values by 0.8% with low GI preparations compared to their regular diet. However, in another study that compared the low glycemic index diet and standard diabetic diet, there was no statistically significant difference between the low GI and higher GI diets in relation to HbA1c and fasting blood glucose [29]. A study done by Yusof et al [30] showed that although the effect on HbA1c was not significantly different between the low-GI diet and the higher-GI diet or control, the improvement within the low-GI group was more pronounced and of clinical benefit.…”
Section: Discussionmentioning
confidence: 91%
“…With respect to the systematic review, only nine articles [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] met the criteria for inclusion ( Table 3 ). However, six of these studies [ 28 , 29 , 30 , 31 , 35 , 36 ] were used for the meta-analysis to test the effect of low-GI diet on glycated haemoglobin and fasting blood glucose in patients with type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies [ 28 , 30 , 34 , 35 , 36 ] that reported dietary glycaemic index values, the low-GI diet had significantly ( p < 0.05) lower values than the higher-GI diet or the control. The study by Jenkins et al [ 29 ] also showed that the low-GI diet resulted in lower GI values than the high-cereal fibre diet, although the level of statistical difference was not stated ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations